Evaluating the high-temperature resistance of self-compacting mortar incorporating waste andesite powder as a mineral admixture - Karatas, Mehmet; Bozcan, Emre; Dener, Murat (Ernst & Sohn, 2025)
Significant amounts of waste material are generated at various stages of andesite stone processing, including mining, cutting, and polishing. Despite this, limited research has been conducted on the potential use of waste andesite powder (WAP) as a mineral admixture. The impact of WAP on the high-temperature resistance of cement-based composites remains largely unexplored. This study aims to evaluate the benefits of incorporating WAP as a partial substitute for Portland cement. Self-compacting mortars (SCMs) with varying WAP replacement rates (5%-30%) were produced and subjected to temperatures of 300 degrees C, 600 degrees C, and 900 degrees C. Additionally, ternary mixtures of WAP and silica fume were produced for comparative analysis. The results showed that SCMs containing up to 10% WAP exhibited higher 90-day compressive strength compared to the control sample. Furthermore, WAP inclusion improved high-temperature resistance, and the use of WAP at higher replacement rates was feasible when combined with mineral admixtures possessing high pozzolanic activity, such as silica fume.
Keywords: andesite powder; high-temperature resistance; self-compacting mortar; silica fume